Molecular investigation of adequate sources of mesenchymal stem cells for cell therapy of COVID-19-associated organ failure. (25th November 2020) - Desterke, Christophe; Griscelli, Frank; Imeri, Jusuf; Marcoux, Paul; Lemonnier, Thomas; Latsis, Theodoros; Turhan, Ali G.; Bennaceur-Griscelli, Annelise
Abstract: The use of mesenchymal stem cells (MSC) derived from several sources has been suggested as a major anti-inflammation strategy during the recent outbreak of coronavirus-19 (COVID-19). As the virus enters the target cells through the receptor ACE2, it is important to determine if the MSC population transfused to patients could also be a target for the virus entry. We report here that ACE2 is highly expressed in adult bone marrow, adipose tissue, or umbilical cord-derived MSC. On the other hand, placenta-derived MSC express low levels of ACE2 but only in early passages of cultures. MSC derived from human embryonic stem cell or human induced pluripotent stem cells express also very low levels of ACE2. The transcriptome analysis of the MSCs with lowest expression of ACE2 in fetal-like MSCs is found to be associated in particularly with an anti-inflammatory signature. These results are of major interest for designing future clinical MSC-based stem cell therapies for severe COVID-19 infections. Abstract : The authors report that mesenchymal stem cells (MSC) derived from adult sources express high levels of ACE2, which could facilitate the SARS-Cov2 entry, compared with MSC derived from embryonic or pluripotent stem cell (iPSC)-derived MSC. The latter population could be the most adequate sources for cell therapy of severe COVID-19 infection, as they could be less prone to SARS-Cov2 entry.